Epidemiology of foodborne Norovirus outbreaks in Catalonia, Spain - Martinez, Ana (BioMed Central, 2008)
BACKGROUND: Noroviruses are one of the principal biological agents associated with the consumption of contaminated food. The objective of this study was to analyse the size and epidemiological characteristics of foodborne outbreaks of gastroenteritis in Catalonia, a region in the northeast of Spain. METHODS: In all reported outbreaks of gastroenteritis associated with food consumption, faecal samples of persons affected were analysed for bacteria and viruses and selectively for parasites. Study variables included the setting, the number of people exposed, age, sex, clinical signs and hospital admissions. The study was carried out from October 2004 to October 2005. RESULTS: Of the 181 outbreaks reported during the study period, 72 were caused by Salmonella and 30 by norovirus (NoV); the incidence rates were 14.5 and 9.9 per 100,000 person-years, respectively. In 50% of the NoV outbreaks and 27% of the bacterial outbreaks (p = 0.03) the number of persons affected was ≥10; 66.7% of NoV outbreaks occurred in restaurants; no differences in the attack rates were observed according to the etiology. Hospitalizations were more common (p = 0.03) in bacterial outbreaks (8.6%) than in NoV outbreaks (0.15%). Secondary cases accounted for 4% of cases in NoV outbreaks compared with 0.3% of cases in bacterial outbreaks (p < 0.001) CONCLUSION: Norovirus outbreaks were larger but less frequent than bacterial outbreaks, suggesting that underreporting is greater for NoV outbreaks. Food handlers should receive training on the transmission of infections in diverse situations. Very strict control measures on handwashing and environmental disinfection should be adopted in closed or partially-closed institutions.